Was freedom road a dead end? Socio-economic effects of reconstruction in the American South - Jeffry A. Frieden; Richard S. Grossman; Daniel Lowery (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We investigate how Reconstruction affected Black socio-economic advancement after the American Civil War. We use the location of federal troops and Freedmen's Bureau offices to indicate more intensive federal enforcement of civil rights. We find that Black people made greater socio-economic advances where Reconstruction was more rigorously enforced, and that these effects persisted at least until the early twentieth century, although these advances were weaker in cotton-plantation zones. We suggest a mechanism leading from greater Black political power to higher local property taxes, through to higher levels of Black schooling and greater Black socio-economic achievement.
Keywords: N31; P10; O10; O51; 330; reconstruction; institutions; US Civil War; economic development